Mengartikulasikan tradisi kritis dalam riset kualitatif bidang psikologi di Indonesia - Yulianto, Jony Eko (Konsorsium Psikologi Ilmiah Nusantara, 2024)
The present article responds to an editorial note in Jurnal Psikologi Ulayat, written by Lestari (2021), to further advocate the need to promote critical tradition in conducting qualitative research in psychology in Indonesia. Central in this article is to discuss (1) why critical tradition is vital for qualitative research in Indonesia; and (2) how we articulate critical tradition to our research practices. Drawing on the concepts of phronesis, epistemological violence, and ontological violence, I offer a discussion on the need to develop analyses to address societal issues. By situating the analysis within the socio-historical context of the discipline, the argument of the paper seeks to highlight the centrality of pluralism of approach in psychology to re-centre the role of indigenous people as the subject of the research, instead of the object. Finally, this article offers six ways to enhance the quality of doing qualitative research with indigenous groups in Indonesia.